Design Lighting Quality Based on DIALux Evo 8.1 - R. Febriyursandi; A.Z. Azriyenni; A. Hamzah (JOURNAL OF SCIENCE AND APPLIED ENGINEERING, 2019)
This research develops and implements methods for calculating lighting systems for classrooms in the Khairul Ummah Boarding School. The lumen is used to determine the number of luminaires needed to improve lighting quality following SNI 6197:2011. The number of luminaires obtained from this study was entered into the DIALux Evo 8.1 software. The results obtained of this study indicate that the lighting in the classroom at Khairul Ummah Boarding School didn’t reach the recommended standard, the direct measurement results of the average lighting level of class A was 10.79 lux, while the class X-IPA-3 was 11.66 lux. To improve this condition, class A requires 15 luminaires, and X-IPA-3 requires 12 luminaires. The difference in the results obtained from the two calculations for class A is 0.6%, and X-IPA-3 is 3.4%. Investment costs are needed to improve the lighting system in these classes worth Rp.2,700,000.00 to provide 27 lamps.